Navigating Digital Religious Education: A Schutzian Motive Analysis of Generation Z Students in Indonesia - Muh Ilham Usman; Muthahharah Muthahharah; Abdul Rafi’ Syafaat (LP. Ma'arif Janggan Magetan, 2025)
This study explores the increasing dependence of Generation Z students in Majene, Indonesia, on social media as a primary medium for religious education, analyzed through Alfred Schutz’s phenomenological framework of motives. The research examines how Schutz’s distinction between “because-motives” and “in-order-to motives” elucidates the contextual and aspirational dimensions shaping students’ engagement with digital religious content. While traditional institutions such as mosques and pesantren have historically dominated religious learning, platforms like YouTube, Instagram, and TikTok are now integral to students’ spiritual formation. Using qualitative methods including interviews, observations, and document analysis, the study finds that students’ because-motives stem from the limited availability of youth-oriented programs in mosques, shifting generational media habits, and the appeal of concise online content. Their in-order-to motives reflect aspirations for spiritual growth, deeper understanding of Islamic teachings, and identification with charismatic online preachers. The findings demonstrate that social media functions not merely as a technological tool but as a transformative arena for constructing religious identity. The study underscores the importance of enhancing digital literacy and promoting moderate online religious engagement.